Inhibition of Ubiquitin-specific protease 14 suppresses cell proliferation and synergizes with chemotherapeutic agents in neuroblastoma - Yu, Yang (Mol Cancer Ther, 2019)
Neuroblastoma (NB) is the most common extracranial malignant solid tumor in children, and drug resistance is a major reason for poor outcomes. Elevated proteasome activity plays an important role in NB tumor development and resistance to conventional chemotherapy. Ubiquitin-specific protease 14 (USP14), one of three deubiquitinases associated with the regulatory subunit of the proteasome, is emerging as a potential therapeutic target in multiple tumor types. However, the role of USP14 in NB is yet to be elucidated. We found that USP14 inhibition in NB via knockdown or a specific inhibitor such as b-AP15 suppressed cell proliferation by inducing cell apoptosis. Furthermore, b-AP15 significantly inhibited NB tumor growth in NGP and SH-SY5Y xenograft mouse models. For combination treatment, b-AP15 plus conventional chemotherapeutic agents such as doxorubicin or VP-16 resulted in synergistic anti-tumor effects on NB. Our study demonstrates that USP14 is required for cell viability and is a novel therapeutic target in NB. Moreover, USP14 inhibition may add value in combination therapy due to its powerful synergistic effects in treating NB.